2007
DOI: 10.1007/s10681-007-9444-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybridisation within Brassica and allied genera: evaluation of potential for transgene escape

Abstract: Determining the potential for hybridisation between transgenic crops and their relatives is a major component of risk assessment. Recent assessments of the extent of reproductive compatibility between crops and their relatives draw heavily on existing data from experimental crosses to infer the likelihood of hybridisation and introgression. Since the literature in this area continues to grow at a rapid pace, it is essential that such analyses can be easily updated. We used a database approach to assemble data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 99 publications
4
137
2
Order By: Relevance
“…Some of these vegetables are left unharvested and flower in the following spring. Interspecific hybridization between Brassica crops can occur under natural conditions, although the results of hybridization potential differ among various reports (e.g., Chèvre et al, 2004;FitzJohn et al, 2007;Ford et al, 2006;Jørgensen et al, 1996;Légère, 2005;Sheffler and Dale, 1994;Stewart et al, 2003;Warwick et al, 2003;Wilkinson et al, 2003). Allainguillaume et al (2006) reported that the fitness decline of hybrids between B. napus and B. rapa in the United Kingdom acted as a means of natural biological containment.…”
Section: Provenance and Environmental Concern Of Oilseed Rape Plantsmentioning
confidence: 89%
“…Some of these vegetables are left unharvested and flower in the following spring. Interspecific hybridization between Brassica crops can occur under natural conditions, although the results of hybridization potential differ among various reports (e.g., Chèvre et al, 2004;FitzJohn et al, 2007;Ford et al, 2006;Jørgensen et al, 1996;Légère, 2005;Sheffler and Dale, 1994;Stewart et al, 2003;Warwick et al, 2003;Wilkinson et al, 2003). Allainguillaume et al (2006) reported that the fitness decline of hybrids between B. napus and B. rapa in the United Kingdom acted as a means of natural biological containment.…”
Section: Provenance and Environmental Concern Of Oilseed Rape Plantsmentioning
confidence: 89%
“…Pollen transfer is likely for flowering oilseed rape and also possible for vegetable crop fields (broccoli and cabbage), where there can be occasional early flowering individuals, post-harvest remnant flowering plants, early bolting or unharvested fields, and flowering foundation seed crops. Oilseed rape (B. napus) readily hybridizes in the field with B. rapa (FitzJohn et al, 2007;Jorgensen and Andersen, 1994;Warwick et al, 2003), and Bt transgenes are stably expressed in these crop-wild hybrids (Zhu et al, 2004). Crosses between B. oleracea and wild relatives have been much less studied, so it is difficult to determine a probability of spontaneous hybridization with wild relatives in the field beyond its apparent compatibility with naturalized B. oleracea in our region (Letourneau et al, 2002).…”
Section: Plants and Crop-wild Gene Flowmentioning
confidence: 99%
“…Interspecific studies which successfully used conventional sexual crosses to produce F 1 hybrids are summarized in Table 5 and recently summarized and evaluated with regards to potential for transgene escape in an extensive review by Fitzjohn et al (2007). Many other hybridizations with more distant relatives have been accomplished using embryo, ovary or ovule rescue techniques (reviewed in Warwick et al 2000).…”
Section: Hybridsmentioning
confidence: 99%